IMPROVING STUDENTS’ WRITING MOTIVATION THROUGH MIND MAP SOFTWARE - melgis dilkawati pratama (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The aim of this study was to analyze the effect of using mind map software on writing motivation of pre-service teachers. The research applied a quasi-experimental design, with a pretest-posttest non-equivalent group. The research employed 42 pre-service teachers taking “Scientic Writing”, in the six semester at the Faculty of Education and Teacher Training at Sultan Syarif Kasim State Islamic University, Indonesia, by using cluster-random sampling. This research used a questionnaire and in-depth interview. T-test was used to analyze the data. The study revealed that the experimental group performed higher motivation than control group in writing. Besides, this group also demonstrated their writing is only for their own interest and satisfaction, not for grading. In contrast, this group showed lower motivation when they worked on mechanical aspects of writing. Overall, this study indicated that the use of a mind map software improves students’ writing motivation.